Anxiety Reactions and Coping Modalities with the COVID-19 Pandemic: A Cross-Sectional Study Comparing a Population of Religious Patients with Mental Illness and their Health Caregivers - Serfaty, David R. (Journal of religion and health, 2021)
This study evaluates the nature and intensity of anxiety, interpretations of the COVID-19 pandemic and coping modalities of hospitalized patients with mental illness compared with their caregivers. One hundred and fifty-one subjects were evaluated with a specially designed questionnaire. Psychiatric inpatients reported more anxiety and more negative feelings than staff members and healthy subjects, but inpatients felt protected by the hospital and Ministry of Health (MoH) measures. Despite this anxiety, inpatients reported a lower compliance with MoH instructions than staff and healthy subjects and gave more fatalistic interpretations to the pandemic. Haredi study participants reported less anxiety, more optimism and had a higher sense of control regarding the pandemic compared to non-religious participants.